Comparação e validação de metodologias moleculares para diagnóstico da meningite tuberculosa - Palomo, Flavia Silva [UNIFESP] (2016)
Tuberculosis meningitis is a severe form of extrapulmonary tuberculosis, because of its high morbidity and mortality. The most common agents of this disease are the mycobacteria of the M. tuberculosis? complex. Definitive diagnosis includes smear that have low sensitivity and culture that delay in diagnosis. The use of molecular methods is promising in the diagnosis of this disease, since they are fast with high, sensitivity and specificity. This study aimed to compare and to validate molecular protocols (PCR) for the diagnosis of tuberculosis meningitis directly from CSF samples including the mycobacterium DNA extraction techniques and targets for PCR amplification. Methods: For comparison and validation of molecular protocols we used positive control group (CSF pools known negative and infected with ATCC M. tuberculosis), negative control group and clinical CSF samples. Four DNA extraction techniques (Phenol-Chloroform-Thiocyanate guanidine, Thiocyanate-Silica guanidine, Resin and Resin with ethanol) were compared. Also, the negative and positive control groups and CSF samples were used to determine the best target (IS6110, and MPB64 hsp65KDa) for diagnosis of tuberculosis meningitis. For statistical analyzes the CSF samples were classified as true positive and negative. For this classification a survey in the site TBweb was done with analysis of laboratory data and medical records of patients. Results: The extraction protocol using the phenol chloroform-thiocyanate guanidine showed the best results in terms of quantification and sensitivity of PCR amplification, presenting up to 10 times more DNA than the second best (silica guanidine thiocyanate). The targets that showed the best amplification results was the the IS6110, with a good agreement (0.64 ?) in conventional PCR and moderate (0.54 ?) in real-time PCR. The sensitivity and specificity were, respectively, 100 % and 79 % for the real-time PCR method and 94 % and 87 % for conventional, when compared to culture. The sample analysis for IS6110 real-time PCR amplification showed a 91% sensitivity, 97% specificity and optimal agreement (0.89 ? ) with the clinical diagnosis . When this analysis was grouped by patient, we showed a sensitivity of 100 % , specificity of 98 % and a very good agreement ( ? 0.96 ) with the clinical diagnosis. Conclusion: A protocol using extraction with phenol chloroform and guanidine thiocyanate, followed by amplification of the IS6110 target for real time PCR in house showed to be suitable for molecular diagnosis of tuberculosis meningitis in our clinical setting.